(untitled) (Journal of the College of Basic Education, 2022)
The current research was conducted in Iraq, Diyala and aims to evaluate the questions of the general (ministerial) exams for Arabic grammar for the sixth grade of middle school for Islamic secondary schools, and the research was limited to the analysis of three copies of the general exam questions for the academic years (2018-2019-2020) the researcher followed the method of analysis The content for conducting the research, and the sample of the analysis amounted to (148) test items of (52) items for the year (2018), (43) items for the year (2019) and (53) items for the year (2020). , The researcher prepared analysis form verified the stability of the analysis of the questions, so the rate of stability of the analysis reached (0.90) and after tabulating the data and treating it statistically using the percentage and Scott’s equation, the study concluded that the level of remembering ranked first with a rate of (51.17%) of the percentage of the analyzed questions, and understanding ranked first. The second place with a percentage of (33.39%), the application ranked third with a rate of (10.08%), and the analysis ranked fourth with a percentage of (5.36%). The study recommended Develop general exam questions, suggested study By conducting similar studies to evaluate questions in other branches of the Arabic language and conducting assessment studies on an ongoing basis and conducting similar studies according to new standards.